PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA CYBERBULLYING BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Ahmad Fauzi; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Bullying is the use of violence, threats, or coercion to harass or intimidate others. This can include verbal harassment or threats, physical violence or coercion and can be directed repeatedly against certain victims, perhaps based on race, religion, gender, sexuality, or ability. The purpose of this study is to determine the legal protection of children who are victims of criminal acts of cyberbullying based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and to determine obstacles in the legal protection of children become a victim of the crime of cyberbullying.The type of research the author will do is use a normative legal research method in which the aim of this study is the degree of legal synchronization. In this writing the writer uses secondary data. Secondary data is data obtained through other intermediaries not from the main source, in the form of official documents, books, research results in the form of reports, diaries and so on.The results of the study by the author are first, the legal protection of cyberbullying crimes has not proceeded properly because of the lack of security and supervision of the apparatus, an imbalance in the number of law enforcement personnel. Secondly, Law No. 19 of 2016 amending Law No. 11 of 2008 concerning Electronic Transactions was born on the basis of community needs and is no longer relevant to continue implementing. Hoping this ITE regulation must be able to work together in terms of providing optimal legal protection to the community, especially in this case children. Because children are the assets of the nation's successors who can continue the struggle of the state apparatus in terms of creating justice, order and the legal benefits inherent as constitutional rights for the creation of the rule of law.Keywords: Legal Protection - Criminal Acts - Cyberbullying.